Development of a passive sensor for measuring vertical cumulative water and solute mass fluxes in lake sediments and streambeds. (July 2017) - Layton, Leif; Klammler, Harald; Hatfield, Kirk; Cho, Jaehyun; Newman, Mark A.; Annable, Michael D.
Highlights: We present a device (SBPFM) for simultaneous measurement of water and contaminant mass fluxes in sedimentary lake and stream beds. The SBPFM is a passive sampler directly driven into the sediment bed to intercept vertical flow and transport. Tracer losses and contaminant retention on a sorbent material are used to estimate cumulative fluxes over the period of exposure. Abstract: This paper introduces the sediment bed passive flux meter (SBPFM) as a new tool for in situ measurements of vertical volumetric water and contaminant mass fluxes across hyporheic and hypolentic zones (i.e., stream or lake bed sediments that function as the contiguous zone between the overlying surface water body and the underlying aquifer). The device is a direct-push probe which contains a permeable internal sorbent located between two screened intervals. In the presence of a vertical hydraulic gradient the screens allow water flow through the SBPFM's internal sorbent matrix that is impregnated with resident tracers. These tracers are displaced from the sorbent at rates proportional to the water flux through the sorbent. At the same time, dissolved contaminants present in the intercepted sediment water are retained on the SBPFM sorbent at rates proportional to the ambient contaminant mass flux in the hyporheic zone. Potential flow theory is applied to convert observations of water and contaminant fluxes through the SBPFM into estimates of undisturbed ambient vertical water and contaminant fluxes in the sediment. To validate the theory and demonstrate the SBPFM as a potential site characterization tool, multiple bench-scale sediment bed experiments are performed. Results demonstrate that water and contaminant mass fluxes are accurately measured in the laboratory and that future field tests are warranted.